The biological effects of powders plants and inert dusts and terpeniod compound Leaves Extract of Concorpus lancifolius Engl. on some adult insects stores - Mohmed, Ahmed Saeed (Journal of Kerbala for Agricultural Sciences, 2015)
The study deals for purpose with the effect of powders of plants and Inert Dusts and terpeniod compound Leaves Extract of Concorpus lancifolius Engl. against adult lesser grain borer and red flour beetles. The mortality rates of adult lesser grain borer When using at concentrations of 15 ,15%(weight by weight) and 30 mg/ml after 7 days of treatment 12.92, 11.02 , 14.18 %respectively , The mortality rates of adult red flour beetles13.76,12.46 ,12.00% when used the same concentrations compared with1.91% in the control treatment. The results showed the effect of powders of plants and Inert Dusts and terpeniod compound Extract was not effected on seed germination of wheat laboratory.